The influence of work engagement, work motivation, resilience, and job stress on the job satisfaction of honorary teachers in Central Java - Aulia, Aulia; Samudra, Rosiani; Ermawati, Diyan; Sidiq, Faiq Ja'far; Asy-Syifa, Shafa Rifda (Universitas Ahmad Dahlan, 2025)
This study examines the influence of work engagement, work motivation, resilience, and job stress on the job satisfaction of honorary teachers in Central Java. The research employs a quantitative approach utilizing a cross-sectional study design. The population for this study consists of honorary teachers who instruct at elementary and high schools in Central Java, with a minimum of five years of teaching experience and a willingness to participate as research subjects. The sampling technique employed was purposive sampling, which resulted in 384 participants. Data collection instruments included job satisfaction, work engagement, work motivation, resilience, and job stress scales. The results of the multiple regression analysis indicate a coefficient of determination (R) of 0.965, an F-value of 1301.778, and a p-value of 0.000 (p < 0.001). Based on these findings, it can be inferred that work engagement, work motivation, resilience, and job stress collectively influence the job satisfaction of honorary teachers in Central Java. Furthermore, the study revealed that resilience contributes more significantly to job satisfaction than the other variables. Therefore, local government initiatives to improve job satisfaction among honorary teachers in Central Java should focus on various strategies, particularly by providing programs for adaptive skills development and problem-solving, such as stress management training, to bolster the resilience of honorary teachers in coping with working pressures.